Policy Enforcement upon Software Based on Microservice Architecture - Asik, Tugrul; Selcuk, Yunus Emre (IEEE, 2017)
Microservice is an architectural style that has recently started gaining popularity to become a new architectural phenomenon. Microservice architecture provides new opportunities to deploy scalable, language free and dynamically adjustable applications. This type of applications consist of hundreds or more of service instances. So that, management, monitoring, refactoring and testing of applications are more complex than monolithic applications. Therefore, some metrics and policies for measuring the quality of an application which is based on microservice architecture is needed. Moreover, automated tools are needed to carry out those tasks and enforce those policies. This work represents such metrics and policies. Additionally, an automated tool is implemented for automatic analysis of those metrics and policies upon software.
Keywords: Microservice architecture; software metrics; software policies; software quality; static analysis tool; Computer Science; Engineering